2017
DOI: 10.3345/kjp.2017.60.3.70
|View full text |Cite
|
Sign up to set email alerts
|

Maternal food restrictions during breastfeeding

Abstract: PurposeThis study investigated self-food restriction during breastfeeding, reviewed the literature showing the effect of maternal diet on the health of breast-fed infants, and explored the validity of dietary restrictions.MethodsQuestionnaire data were collected from breastfeeding Korean mothers who visited the pediatric clinic of Cheil General Hospital & Women's Healthcare Center from July 2015 through August 2015. The survey included items assessing maternal age, number of children, maternal educational atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…The calorie-rich dietary pattern with high milk and milk product consumption is an age-old tradition among Indian women where they are fed more milk with the notion that it would enhance their breast milk production. The study, based on the GUSTO birth cohort, also reported similar results (34). The study mentioned that the consumption of leafy vegetables and milk-based drinks increased post-pregnancy among Indian participants compared to the pre-pregnancy period from 47.1 to 73.4% (p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…The calorie-rich dietary pattern with high milk and milk product consumption is an age-old tradition among Indian women where they are fed more milk with the notion that it would enhance their breast milk production. The study, based on the GUSTO birth cohort, also reported similar results (34). The study mentioned that the consumption of leafy vegetables and milk-based drinks increased post-pregnancy among Indian participants compared to the pre-pregnancy period from 47.1 to 73.4% (p < 0.001).…”
Section: Discussionsupporting
confidence: 53%
“…It is known that the mother's diet directly affects the quality and quantity of the produced milk. Despite that, there are significant rates of maternal malnutrition in developing and developed countries [1,2,[4][5][6]19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, maternal malnutrition rates are still fairly high among the general population. Hence, it is still a public health issue in developing or underdeveloped countries [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not only a product of noningestion of food, since irregular dietary habits such as excessive fast food ingestion can cause this condition (Ahsan et al, 2017;Kavle et al, 2018). Despite numerous governmental programs and campaigns, there is still a high incidence of pregnant and lactating women that have an inadequate nutrient intake (Black et al, 2013;Haileslassie et al, 2013;Jeong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%